Opinion '90 - Weibull, Lennart (University of Gothenburg, 1992)
One of the topics of this survey is reading habits and attitude to the local information paper 'Vårt Göteborg', published by the municipality of Göteborg. Six times a year the paper is distributed freely to all households in Göteborg. The paper as a source of information is compared with other media. Another topic of this survey was the introduction of neighbourhood committees. The respondent had to give an opinion on how well informed she/he was about the neighbourhood committees, if there had been any information at all about the introduction of the committees, and if so, what kind of sources of information there had been. Other questions dealt with the respondents attitude to and knowledge about the committees. The third topic of this survey was the shipping company Stena Line from an environmental viewpoint. Questions were asked about what environmental actions one believed had been taken from the company and if one had paid attention to the campaign 'Levande Kattegatt'. Other questions dealt with the respondent's own environmental activities.

One of the topics of this survey is reading habits and attitude to the local information paper 'Vårt Göteborg', published by the municipality of Göteborg. Six times a year the paper is distributed freely to all households in Göteborg. The paper as a source of information is compared with other media. Another topic of this survey was the introduction of neighbourhood committees. The respondent had to give an opinion on how well informed she/he was about the neighbourhood committees, if there had been any information at all about the introduction of the committees, and if so, what kind of sources of information there had been. Other questions dealt with the respondents attitude to and knowledge about the committees. The third topic of this survey was the shipping company Stena Line from an environmental viewpoint. Questions were asked about what environmental actions one believed had been taken from the company and if one had paid attention to the campaign 'Levande Kattegatt'. Other questions dealt with the respondent's own environmental activities.
Opinion '90
Keywords: Media; Media; Information society; Informationssamhället; Environment and conservation; Miljö och naturvård; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap